IMPLEMENTASI MULTIPLE MIND MAPPING DALAM KELAS EXTENSIVE READING - Chasanatum, Fida; Lestari, Sri; Wahyuni C., Tri (IKIP PGRI MADIUN, 2013)
Orientation: An Extensive Reading Class is the last reading class taken by the students of English teaching department. It is essential for them toÂ cope all the problems with international journal articles. This research is placing this matter and giving one solution for their problems.Research Purpose: The objectives of this research were to establish studentsâ abillity in reading several theories from international journal articles and writingÂ an analyzing composition for their academic eading and writing skills.Motivation for the study: The research provides a starting point in identificating technical terms in articles, relating one similar to athers, synthezising them in a composition, and understanding in supporting their main opinion. This will shape their way of thinking when involving their opinion to academic authentic materials learnt.Reasearch design, Approach, and Method: The participants of this research consists of 120 fourth semester students in IKIP PGRI MADIUN, which take Extensive Reading Class taught by three lectures. Collaborative Action Research is applied in handing the documentations, interviews, and observations as the data sources.Main Findings: Results came from two cycles. The cycle one main findings are students need a help from individual vocabulay list for ease them in finding the similarity amongs words, the preceference of lecturers in guiding and giving their solution in reading problems, the need of a handbook in forming the border of studentsâ journal finding, and increasing studentsâ motivation in writing what their read. The findings of the second cycle are the vocabulay list help the students, the students lack of motivation in reading solved by the teachersâ guidence in eased them, this reseach helps the students in encreasing their ability in writing, and promote them in deciding their ideas for final assignment as an academic students.Contribution/Value-add: The process leads the lecturers in collaboratively handling studentsâ difficulties. It also showed the students the proper way of citation, understanding, and synthesizing the terms related to the ideas they had.